Energy Efficiency Enhancement of Fossil-Fuelled Power Systems - Palanichamy, Chinnasamy; Naveen, Palanichamy; Kiing Ing, Wong; Danquah, Michael Kobina; Indumathi, J. (International Journal of Energy Economics and Policy, 2015)
Energy efficiency is the simplest and cost-effective approach for power and process industries to meet a growing demand for cleaner energy, and this applies to the power generating industries as well. Energy efficiency of fossil-fuelled power systems in developed as well as developing countries is abnormally low, consuming high quantity of fuel to generate per unit electricity, which is a fundamental issue throughout the globe. Though energy efficiency improvements are possible at all sections of a power system, this paper put forward an energy efficiency enhancement opportunity at the power generation station itself by proper scheduling of the generating units. To show the efficacy of the proposed strategy, an economic dispatch algorithm has been applied to several dissimilar realistic systems at different load conditions and the outcome of one such realistic system is presented in this paper. Keywords: Energy efficiency enhancement; fossil-fuelled power systems; generation scheduling JEL Classifications: B4; C8; L8; O1; O3